CALCAREOUS NANNOFOSSIL BIOSTRATIGRAPHY OF THE S’ADDE LIMESTONE (MT. ALBO, OROSEI GULF): INSIGHTS INTO THE MIDDLE-LATE JURASSIC EASTERN SARDINIA PASSIVE MARGIN EVOLUTION (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
Calcareous nannofossil biostratigraphy has been performed on tree sections cropping out in Eastern Sardinia (Orosei Gulf, Mt. Albo). Calcareous nannofossils are rare to few and poorly to moderately preserved. Nevertheless thirteen bioevents have been recognized (S’Adde valley section) and a Late Bathonian-Early Tithonian age is derived for the S’Adde Limestone (Lms.). The inferred age constraints, integrated with data from the literature, allow the revision of the S’Adde Lms. chronostratigraphy, and the formalization of the S’Adde Limestone (Dieni & Massari 1985) as a lithostratigraphic unit. Qualitative evaluations of carbonate production/sedimentation rates for the north Mt. Albo area are proposed: the Late Bathonian-Callovian and Oxfordian were times of pronounced reduction of carbonate production/exportation, in agreement with the European passive margin evolution, also affected by starvation fenomena and condensations. A Middle-Late Jurassic basin-and-swell setting related to regional tensional tectonic activity is reconstructed for the north Mt. Albo area. The comparison of new and literature data allows framing the local and Eastern Sardinia passive margin evolution in the broader geodynamic and paleogeographic context of the southern European margin.
Keywords: Callovian-Early Tithonian; Eastern Sardinia; S’Adde Limestone; calcareous nannofossil; hardground; south European passive margin